Grammar and Vocabulary for First Certificate - Prodromou L. Luke (Harlow, Longman, 2010)
Designed for upper intermediate students an innovative approach particularly relevant to the Cambridge First Certificate in English (FCE) exam. Thorough grammar reviewdetailed information concentrating on points tested in the exam, and a wealth of examples based on the Longman Corpus a focus on vocabulary concentration on word formation, confusible words, and on common words and phrases that are useful in numerous situations. Lots of opportunity to practisea wide variety of exercises to confirm understanding and prepare for the FCE exam, particularly Paper 3continuous testing in exam format, a diagnostic test for each Unit and regular tests in exam format to check progress, a flexible approach, can be used in many different ways; clear cross-references point you in the direction of related grammar or vocabulary areas